KI 2017 : advances in artificial intelligence : 40th Annual German Conference on AI, Dortmund, Germany, September 25-29, 2017, Proceedings /: advances in artificial intelligence : 40th Annual German Conference on AI, Dortmund, Germany, September 25-29, 2017, Proceedings. (2017) - Unknown
No abstract available